Properties of Retinal Precursor Cells Grown on Vertically Aligned Multiwalled Carbon Nanotubes Generated for the Modification of Retinal Implant-Embedded Microelectrode Arrays - Sandra Johnen; Frank Meißner; Mario Krug; Thomas Baltz; Ingolf Endler; Wilfried Mokwa; Peter Walter (Journal of Ophthalmology)
Background. To analyze the biocompatibility of vertically aligned multiwalled carbon nanotubes (MWCNT), used as nanomodification to optimize the properties of prostheses-embedded microelectrodes that induce electrical stimulation of surviving retinal cells. Methods. MWCNT were synthesized on silicon wafers. Their growth was achieved by iron particles (Fe) or mixtures of iron-platinum (Fe-Pt) and iron-titanium (Fe-Ti) acting as catalysts. Viability, growth, adhesion, and gene expression of L-929 and retinal precursor (R28) cells were analyzed after nondirect and direct contact. Results. Nondirect contact had almost no influence on cell growth, as measured in comparison to reference materials with defined levels of cytotoxicity. Both cell types exhibited good proliferation properties on each MWCNT-coated wafer. Viability ranged from 95.9 to 99.8%, in which better survival was observed for nonfunctionalized MWCNT generated with the Fe-Pt and Fe-Ti catalyst mixtures. R28 cells grown on the MWCNT-coated wafers showed a decreased gene expression associated with neural and glial properties. Expression of the cell cycle-related genes CCNC, MYC, and TP53 was slightly downregulated. Cultivation on plasma-treated MWCNT did not lead to additional changes. Conclusions. All tested MWCNT-covered slices showed good biocompatibility profiles, confirming that this nanotechnology is a promising tool to improve prostheses bearing electrodes which connect with retinal tissue.